Kesiapan Dan Efektifitas Pelaksanaan Program Merdeka Belajar Kampus Merdeka Pada Universitas Darussalam Ambon - Rapiah Sarfa Marasabessy; Yudhy Muhtar Latuconsina; Soni Ardian; Nunung Triyani; Muhammad Ramdhani Ohorella (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The Independent Learning Campus Independent Program (MBKM) at Darussalam University Ambon is currently only run by two faculties, namely the Faculty of Engineering and the Faculty of Teacher Training and Education. This is due to the low level of knowledge and the lack of availability of policies, as well as facilities and infrastructure to support MBKM. The purpose of this study was to determine the level of knowledge, readiness and effectiveness of the implementation of MBKM at Darussalam University Ambon by using a mix method consisting of survey methods and Focuss Group Discussions. The results of the survey research indicate that the level of knowledge of lecturers, education staff, students, and heads of study programs is in the good category, while the level of readiness and effectiveness is low. The survey results were further discussed in a focus group discussion by presenting external and internal speakers and attended by students, lecturers, education staff and leadership elements from study programs, faculties, and universities. The results of the FGD were in the form of recommendations containing: Adjustment of the STATUTA of Darussalam University Ambon, Adjustment of the Academic Regulations of Darussalam University of Ambon, Preparation of Quality Standards Related to MBKM, Preparation of guidelines for the MBKM Program of Darussalam Ambon University, and Provision of instruments for implementing and evaluating the MBKM program for each MBKM activity